Electric-field induced spin accumulation in the Landau level states of topological insulator thin films. (21st July 2017) - Siu, Zhuo Bin; Chowdhury, Debashree; Basu, Banasri; Jalil, Mansoor B A
Abstract: A topological insulator (TI) thin film differs from the more typically studied thick TI system in that the former has both a top and a bottom surface where the states localized at both surfaces can couple to one other across the finite thickness. An out-of-plane magnetic field leads to the formation of discrete Landau level states in the system, whereas an in-plane magnetization breaks the angular momentum symmetry of the system. In this work, we study the spin accumulation induced by the application of an in-plane electric field to the TI thin film system where the Landau level states and inter-surface coupling are simultaneously present. We show, via Kubo formula calculations, that the in-plane spin accumulation perpendicular to the magnetization due to the electric field vanishes for a TI thin film with symmetric top and bottom surfaces. A finite in-plane spin accumulation perpendicular to both the electric field and magnetization emerges upon applying either a differential magnetization coupling or a potential difference between the two film surfaces. This spin accumulation results from the breaking of the antisymmetry of the spin accumulation around the k -space equal-energy contours.